Do the Type of Sukuk and Choice of Shari'a Scholar Matter? - Godlewski, Christophe (IMF Working Papers; Working Paper, 2014)
Sukuk, the shari'a-compliant alternative mode of financing to conventional bonds, have expanded considerably over the last decade. We analyze the stock market reaction to two key features of this financial instrument: sukuk type and characteristics of the shari'a scholar certifying the issue. We use the event study methodology to measure abnormal returns for a sample of 131 sukuk from eight countries over the period 2006-2013 and find that Ijara sukuk structures exert a positive influence on the stock price of the issuing firm. We observe a similar positive impact from shari'a scholar reputation and proximity to issuer. Overall our results support the hypotheses that the type of sukuk and the choice of scholars hired to certify these securities matter for the market valuation of the issuing company.